The influence of islamic work ethics on organizational performance at the Islamic Banking Institutions in Aceh / Azharsyah - Azharsyah, - (2015)
This research was motivated by the relatively low research carried out in Islamic Work Ethics (IWE), slow innovation in the IWE scale, and unethical conducts happening with the case of Islamic banks. The general purpose of this research was to seek a better understanding of the notion of IWE and its implementation at the Islamic Banking Institutions (IBIs) in Aceh. In specific, it examines the influence of IWE towards the organizational performance through four non-financial performance factors, namely job satisfaction, organizational commitment, turnover intention, and customer satisfaction. The IWE and customer satisfaction were measured using self-developed instruments, while job satisfaction, organizational commitment, and turnover intention were scaled using modified instruments. In collecting the data, the study employed a quantitative research approach using questionnaire surveys. The surveys were distributed to 868 employees and customers of seven selected Islamic banks. The data was analyzed using SPSS software with its descriptive and inferential analyses. The findings presented IWE in the form of five principles, eight dimensions and 44 values, which were used as the basic for the instrument development. The core value of Islamic ethics promotes goodness for all human beings regardless of countries, cultures, race, educational background, and many local values. The study highlighted the significant positive impact of IWE on job satisfaction, organizational commitment and customer satisfaction, while at the same time showed negative impact on turnover intention. The findings clearly demonstrate the important task of creating an Islamic ethical environment within organizations, especially the IBIs. Therefore, it is hoped that these findings could be used as a guideline for organizations, especially the IBIs, in promoting the Islamic ethical values within their organizations in order to boost the organizational performance.